Optimization of Digital Library Management in the Era of Educational Technology - Agusalim (Institute Journal and Publication Muhammadiyah University of Buton, 2025)
This study aims to examine the optimization of digital library management in supporting learning at Public Senior High School 6 Baubau, particularly in relation to improving access to learning resources, integrating information technology, and fostering collaboration among stakeholders. The research employs a qualitative approach with data collected through in-depth interviews, observation, and documentation involving grade X and XI teachers, grade X and XI students, and the school librarian. The findings indicate that the digital library significantly expands students’ access to various learning resources such as e-books, electronic journals, and interactive learning media that support independent learning. Moreover, the application of information technology through online catalogs and app-based lending systems has enhanced the efficiency of library services. School management has provided strong support through the provision of digital infrastructure, system development, and training for teachers and librarians. Positive collaboration between teachers and librarians in developing curriculum-aligned digital learning materials further strengthens the integration of the library into the learning process. In conclusion, the digital library plays a crucial role in shaping a modern learning ecosystem that is inclusive, efficient, and adaptive to the development of educational technology, while also enhancing digital literacy and active student participation in the school environment.